Особливості інтродукції видів роду Ерірасtis Zinn (Orchidaceae Juss.) у Національному ботанічному саду ім. М.М. Гришка НАН України - Gaponenko, M.B. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2013)
Introduction of some species of genus Ерірасtis Zinn belonging to the natural flora of Ukraine was studied in M.M. Gryshko National Botanical Gardens of the NAS of Ukraine. Biological, morphological and ecological features of plants of introduction populations are investigated. It is shown that successful introduction of species of genus Ерірасtis Zinn for the purpose of their preservation and repatriation in the conditions of culture is possible.